Defining the Ischemic Penumbra Using Magnetic Resonance Oxygen Metabolic Index. Issue 4 (April 2015) - An, Hongyu; Ford, Andria L.; Chen, Yasheng; Zhu, Hongtu; Ponisio, Rosana; Kumar, Gyanendra; Shanechi, Amirali Modir; Khoury, Naim; Vo, Katie D.; Williams, Jennifer; Derdeyn, Colin P.; Diringer, Michael N.; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— Penumbral biomarkers promise to individualize treatment windows in acute ischemic stroke. We used a novel magnetic resonance imaging approach that measures oxygen metabolic index (OMI), a parameter closely related to positron emission tomography–derived cerebral metabolic rate of oxygen utilization (CMRO2), to derive a pair of ischemic thresholds: (1) an irreversible-injury threshold that differentiates ischemic core from penumbra and (2) a reversible-injury threshold that differentiates penumbra from tissue not-at-risk for infarction. Methods— Forty patients with acute ischemic stroke underwent magnetic resonance imaging at 3 time points after stroke onset: <4.5 hours (for OMI threshold derivation), 6 hours (to determine reperfusion status), and 1 month (for infarct probability determination). A dynamic susceptibility contrast method measured cerebral blood flow, and an asymmetrical spin echo sequence measured oxygen extraction fraction, to derive OMI (OMI=cerebral blood flow×oxygen extraction fraction). Putative ischemic threshold pairs were iteratively tested using a computation-intensive method to derive infarct probabilities in 3 tissue groups defined by the thresholds (core, penumbra, and not-at-risk tissue). An optimal threshold pair was chosen based on its ability to predict infarction in the core, reperfusion-dependent survival in the penumbra, and survival in not-at-risk tissue. The predictive abilities of the thresholds were then tested within the same cohort using a 10-fold cross-validation method. Results— The optimal OMI ischemic thresholds were found to be 0.28 and 0.42 of normal values in the contralateral hemisphere. Using the 10-fold cross-validation method, median infarct probabilities were 90.6% for core, 89.7% for nonreperfused penumbra, 9.95% for reperfused penumbra, and 6.28% for not-at-risk tissue. Conclusions— OMI thresholds, derived using voxel-based, reperfusion-dependent infarct probabilities, delineated the ischemic penumbra with high predictive ability. These thresholds will require confirmation in an independent patient sample.